Utilization Of Butterfly Pea Flower Extract On The Characteristics Of Putu Ayu - Nopendra, Wilda Dwi; Andriani, Cici; Fridayati, Lucy; Zulfikar, Dikki; Nurhasanah, Nurhasanah (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research is motivated by the increasing use of synthetic dyes in society, industry and the market. To reduce dependence on synthetic dyes, natural dyes such as butterfly pea flowers can be used as a substitute for synthetic dyes. Butterfly pea flowers have many health benefits. The benefits of butterfly pea flower extract as a natural dye in making putu ayu can reduce the use of synthetic dyes and can introduce the public that butterfly pea flowers have many benefits. This research aims to analyze the use of telang flower extract as much as 25%, 50% and 75% on the quality of putu ayu which includes shape, color, aroma. This type of research is an experiment with a completely randomized design method with one factor. The type of data is primary data sourced from 3 expert panelists with an organoleptic test filling format. The data obtained were tabulated in table form and analysis of variance (ANOVA) was carried out, if different, continued with the Duncan test. The use of butterfly pea flower extract as a natural dye affects the color quality (blue bottom) and texture (soft).